Construction technology students’ behavioural intentions towards Game-Based Learning (GBL) in Malaysia: conceptual framework / Wan Nur Syazwani Wan Mohammad ... [et al.] - Wan Mohammad, Wan Nur Syazwani; Ahmad Zamri, Nurhasyimah; Raja Nhari, Raja Nurulhaiza; Zulkifli, Mohd Zul Aswad; Talkis, Nor Azizah (Universiti Teknologi MARA, Kedah, 2023)
Virtual learning has become increasingly popular in higher education, with virtual laboratories and technology-enhanced experiential learning tools (i.e., digital games), and is expected to become even more important. However, despite the development of these tools, construction technology students, particularly those studying structural subjects, are still reluctant in applying these tools and use technology relatively infrequently. This is due to the lack of Game-Based Learning (GBL) (i.e., digital or non-digital games) frameworks in the literature that are specific to the students' behavioral intentions. This can lead to difficulties for structural students in understanding the subject matter. To address this issue, this study proposes a conceptual framework for GBL (i.e., digital or non-digital games) specifically related to the students' behavioral intentions, concentrating on structural students from construction technology programs in Malaysia. Six additional external constructs (i.e., subjective norm, syllabus connectedness, learning opportunities, experience with technology, self-efficacy, and enabling environment) to the original constructs of the Technology Acceptance Model (TAM) (i.e., perceived usefulness and perceived ease of use) are determined. The expected results include the relevance of the previously established constructs, perceived ease of use, perceived usefulness, and six external constructs as well as the hypothesized relationships among these constructs with reference to TAM. The conceptual framework aims to assess the student's performance in understanding structural subjects which then serves as a theoretical base for the development of GBL (i.e., digital or non-digital games) for structural students in Malaysia's construction technology programs.